MANAJEMEN PENGEMBANGAN PRESTASI ATLET RENANG KOMPETITIF: STUDI KASUS DI KOTA PALEMBANG - Harrismunandar, Septian; Martinus; Endrawan, I Bagus; Fikri, Aprizal (JURNAL ILMU KEOLAHRAGAAN, 2025)
This study addresses the declining trend in competitive swimming achievements in Palembang City, despite the sport’s potential to produce elite athletes. The research aims to evaluate the management of athlete development using the POAC framework (Planning, Organizing, Actuating, and Controlling) to identify strengths, weaknesses, and improvement strategies. A qualitative descriptive approach was employed, involving observations, semi-structured interviews, and document analysis with 20 participants, including administrators, coaches, and athletes. The findings reveal that planning is carried out through structured short-term, medium-term, and long-term programs aligned with competition calendars; organizing involves clear role distribution and active coordination among stakeholders; actuating is implemented via systematic training schedules, adequate facilities, and motivational support; and controlling is conducted through regular evaluations of performance and discipline. Scientific evidence indicates that while the organizational structure and program planning are strong, challenges remain in funding, sponsorship, and coach capacity. It is concluded that sustainable competitive success requires increased resource allocation, facility upgrades, and the integration of sports science into training programs